Information integration theory and functional measurement - Martišius, V. (Psichologija, 1982)
The theories of information integration and functional measurement suggested by Anderson are reviewed. The use of functional measurement in psychophysics, psychological decision theory and developmental psychology is considered. It is concluded that this approach is important for research in various psychological areas.